Beyond the two‐group paradigm in studies of intergroup conflict and inequality: Third parties and intergroup alliances in xenophobic violence in South Africa. (26th November 2016) - Kerr, Philippa; Durrheim, Kevin; Dixon, John
Abstract : Social psychologists typically conceptualize intergroup processes in terms of unequal pairs of social categories, such as an advantaged majority (e.g., 'Whites') and a disadvantaged minority (e.g., 'Blacks'). We argue that this two‐group paradigm may obscure the workings of intergroup power by overlooking: (1) the unique dynamics of intergroup relations involving three or more groups, and (2) the way some two‐group relationships function as strategic alliances that derive meaning from their location within a wider relational context. We develop this argument through a field study conducted in a grape‐farming town in South Africa in 2009, focusing on an episode of xenophobic violence in which a Zimbabwean farm worker community was forcibly evicted from their homes by their South African neighbours. Discursive analysis of interview accounts of the nature and origins of this violence shows how an ostensibly binary 'xenophobic' conflict between foreign and South African farm labourers was partially constituted through both groups' relationship with a third party who were neither victims nor perpetrators of the actual violence, namely White farmers. We highlight some potential political consequences of defaulting to a two‐group paradigm in intergroup conflict studies.